Design Improvement of Disposable Food Containers to Improve Weight Capacity and Reduce Structure Flimsy - Nur Amirah Othman; Muhammad A’imullah Abdullah (Progress in Engineering Application and Technology, 2024)
The project addresses the contemporary significance of disposable food containers in Malaysia, exploring their widespread use and the associated environmental challenges. The ubiquity of these containers in the food industry, driven by their convenience and practicality, has led to concerns about their environmental impact. In response to user feedback on social media platforms like Twitter, advocating for a redesign, this research aims to enhance the design of the commonly used PP-LB02T food disposable container. The study employs SolidWorks 2022, an engineering-based software, to analyse the impact of enlarging the container’s curve diameter on factors such as stress, strain, and material suitability. The methodology involves taking readings with different curve parameters of 4mm, 5mm, and 6mm and utilising simulation analysis to calculate the percentage difference in Von Misses’ values between the original and redesigned food disposable containers. The evaluation of Von Mises stress and displacement may be carried out on a three-dimensional product by the use of Finite Element Analysis. Through the use of this computational technique, useful insights into structural integrity are obtained, which helps in the optimisation of design and ensures that the product’slongevity and performance are up to the standards that are sought. Through this innovativeapproach, the study seeks to contribute to the ongoing discourse on sustainable alternatives in food packaging. Furthermore, it examines consumers’ opinions to understand the determinants influencing the acceptance and selection of eco-friendly options, acknowledging the importance of aligning design modifications with consumer preferences. By addressing issues of food waste reduction and surface fragility in terms of reinforcement, the study emphasises the dual role of disposable food containers in preserving food quality and meeting sustainability goals within the food and beverage industry. The implications of this research extend beyond design innovation, offering insights into more environmentally conscious practices in the food packaging sector